Quantitative analyses of photovoltaic CIGS thin films via SIMS depth profiling with elemental ions and MCs+ clusters - Lee, Jihye; Kim, Seon Hee; Lee, Yeonhee (John Wiley & Sons Inc., 2014)
Polycrystalline copper-indium-gallium-diselenide (CIGS) is used as an absorber in thin-film solar cells because of its appropriate band gap and high absorption coefficient for solar radiation. Many research groups have determined the CIGS compositions related to solar cell efficiency. In this work, three different Cu(In, Ga) Se-2 thin films were prepared on molybdenum back contacts deposited on soda-lime glass substrates via a three-stage evaporation or, alternatively, a two-step selenized process. Surface analyses via AES, XPS, and SIMS were used to characterize the CIGS thin films and compare their depth profiles. The MCs+ clusters were detected to improve the quantification of major compositions in the CIGS thin films while suppressing the matrix effect in the SIMS depth profiles. The compositional distribution in the MCs+-SIMS was in good agreement with the AES and XPS depth profiles. The MCs+-SIMS results proved more quantitatively accurate than those from the elemental SIMS while comparing to ICP-AES data. Copyright (C) 2014 John Wiley & Sons, Ltd.